Occupational risks associated with severe COVID-19 disease and SARS-CoV-2 infection – a Swedish national case-control study conducted from October 2020 to December 2021 - Torén, Kjell; Albin, Maria; Bergström, Tomas; Murgia, Nicola; Alderling, Magnus; Schiöler, Linus; Åberg, Maria (Scandinavian Journal of Work, Environment & Health, 2023)
' ' OBJECTIVE ': 'This study aimed to investigate whether workplace factors and occupations are associated with SARS-CoV-2 infection or severe COVID-19 in the later waves of the pandemic. ' ' METHODS ': 'We studied 552 562 cases with a positive test for SARS-CoV-2 in the Swedish registry of communicable diseases, and 5985 cases with severe COVID-19 based on hospital admissions from October 2020 to December 2021. Four population controls were assigned the index dates of their corresponding cases. We linked job histories to job-exposure matrices to assess the odds for different transmission dimensions and different occupations. We used adjusted conditional logistic analyses to estimate odds ratios (OR) for severe COVID-19 and SARS-CoV-2 with 95% confidence intervals (CI). ' ' RESULTS ': 'The highest OR for severe COVID-19 were for: regular contact with infected patients, (OR 1.37, 95% CI 1.23–1.54), close physical proximity (OR 1.47, 95% CI 1.34–1.61), and high exposure to diseases or infections (OR 1.72, 95% CI 1.52–1.96). Mostly working outside had lower OR (OR 0.77, 95% CI 0.57–1.06). The odds for SARS-CoV-2 when mostly working outside were similar (OR 0.83, 95% CI 0.80–0.86). The occupation with the highest OR for severe COVID-19 (compared with low-exposure occupations) was certified specialist physician (OR 2.05, 95% CI 1.31–3.21) among women and bus and tram drivers (OR 2.04, 95% CI 1.49–2.79) among men. ' ' CONCLUSIONS ': 'Contact with infected patients, close proximity and crowded workplaces increase the risks for severe COVID-19 and SARS-CoV-2 infection. Outdoor work is associated with decreased odds for SARS-CoV-2 infection and severe COVID-19.
Keywords: case-control study; coronavirus; COVID-19; epidemiology; JEM; job exposure matrix; occupation; occupational risk; SARS-Cov-2; Sweden; workplace